2022
DOI: 10.30865/mib.v6i3.4436
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Sentiment Pelanggan Terhadap Penilaian Produk Pada Toko Online Shop Amreta Menggunakan Metode Naïve Bayes Classification

Abstract: Sentiment analysis or opinion mining is an analysis that aims to see the sentiment of people or groups regarding certain entities. The sentiments expressed by society can be in positive, negative and neutral form. One media that can be given an opinion by the public is in the e-commerce application,  namely the shopee application, shopee has a comment or assessment feature on the product that has been purchased. Toko which was used as a sample of researchersis an amreta online shop store  , based on the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Muhammad Muslimin, Tri Herdiawan Apandi, and Didik Garbian Nugroho presented studies focusing on Naïve Bayes classification, attaining accuracy rates of 94.38%, 91.33%, and 80.00%, respectively [2]. A study by Muhammad Muslimin et al in 2023, titled "sentiment Analysis of Rising Basic Commodity Prices Using Naïve Bayes Classifier," concluded that sentiment analysis on increasing basic commodity prices yielded negative responses, achieving an accuracy of 94.38% [1]. Didik Garbian Nugroho's 2016 study, "sentiment Analysis on Online Motorcycle Taxi Services Using Naïve Bayes," achieved an 80% accuracy rate utilizing sentiment data from Twitter [2].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Muhammad Muslimin, Tri Herdiawan Apandi, and Didik Garbian Nugroho presented studies focusing on Naïve Bayes classification, attaining accuracy rates of 94.38%, 91.33%, and 80.00%, respectively [2]. A study by Muhammad Muslimin et al in 2023, titled "sentiment Analysis of Rising Basic Commodity Prices Using Naïve Bayes Classifier," concluded that sentiment analysis on increasing basic commodity prices yielded negative responses, achieving an accuracy of 94.38% [1]. Didik Garbian Nugroho's 2016 study, "sentiment Analysis on Online Motorcycle Taxi Services Using Naïve Bayes," achieved an 80% accuracy rate utilizing sentiment data from Twitter [2].…”
Section: Related Workmentioning
confidence: 99%
“…For instance, Muhammad Muslimin achieved a Naïve Bayes accuracy rate of 94.38%, while Tri Herdiawan Apandi achieved 91.33%, and Didik Garbian Nugroho achieved 80.00% [1]. In a similar study, Muhammad Muslimin et al (2023) conducted research titled "Sentiment Analysis of Rising Basic Commodity Prices Using Naïve Bayes Classifier," concluding that Sentiment analysis of rising basic commodity prices garnered negative responses from the public. The Naïve Bayes method used in the analysis achieved an accuracy of 94.38% [1].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation